Relevancia de la medición del estrés del tejido plantar en la neuropatía diabética - Martínez Pizarro, Sandra (Mediciego, 2020)
Excessive stress on the plantar tissue, over time, is one of the main causes of diabetic foot ulcers in people with diabetic peripheral neuropathy.